High-Mobility Tellurium Thin-Film Transistor: Oxygen Scavenger Effect Induced by a Metal-Capping Layer - Seung-Min Lee; Seong Cheol Jang; Ji-Min Park; Jaewon Park; Nayoung Choi; Kwun-Bum Chung; Jung Woo Lee; Hyun-Suk Kim (Nanomaterials)
With the ongoing development of electronic devices, there is an increasing demand for new semiconductors beyond traditional silicon. A key element in electronic circuits, complementary metal-oxide semiconductor (CMOS), utilizes both n-type and p-type semiconductors. While the advancements in n-type semiconductors have been substantial, the development of high-mobility p-type semiconductors has lagged behind. Recently, tellurium (Te) has been recognized as a promising candidate due to its superior electrical properties and the capability for large-area deposition via vacuum processes. In this work, an innovative approach involving the addition of a metal-capping layer onto Te thin-film transistors (TFTs) is proposed, which significantly enhances their electrical characteristics. In particular, the application of an indium (In) metal-capping layer has led to a dramatic increase in the field-effect mobility of Te TFTs from 2.68 to 33.54 cm2/Vs. This improvement is primarily due to the oxygen scavenger effect, which effectively minimizes oxidation and eliminates oxygen from the Te layer, resulting in the production of high-quality Te thin films. This progress in high-mobility p-type semiconductors is promising for the advancement of high-performance electronic devices in various applications and industries.